Efeito protetor do extrato de lingonberry sobre o sistema purinérgico e estresse oxidativos no sistema nervoso de ratos diabéticos - Reichert, Karine Paula (2015)
Diabetes mellitus (DM) is considered a metabolic disorder that affects large part of worldwide. The hyperglycemia of diabetes cause cognitive impairments associated with physiological and structural changes in the central nervous system (CNS) as well as purinergic signaling. The overproduction of reactive oxygen species (ROS) contributes significantly to the complications of this disease. Fruits that have a variety of polyphenolic compounds, such as Lingonberry (Vaccinium vitis-idaea L.), can modulate the components involved in the purinergic system and prevent damage caused by oxidative stress. Thus, it is intended to investigate the effect of treatment with Lingonberry extract (LB) on the purinergic system and oxidative stress in the cortex of streptozotocin induced diabetic rats. The male Wistar rats were divided into five groups (n = 10): control/saline control/LB 50 mg/kg, diabetic/saline, diabetic/LB 25 mg/kg and diabetic/LB 50 mg/kg treated orally for 30 days. After they were euthanized and the cerebral cortex removed for analysis. Our results demonstrate a reduction in hydrolysis of ATP, ADP and AMP in the diabetic group/saline compared to the control/saline, and treatment with LB at a dose of 50 mg/kg was able to prevent this reduction. For the activity of adenosine deaminase were not found significant results. The expression of P2X7 receptor increased in the diabetic group/saline and as the A1 receptor was decreased in diabetes, treatment at both doses was able to maintain expression of these receptors near the control/saline group. It was also observed an increase in ROS and levels of lipid peroxidation (TBARS) in the diabetic/saline group compared to the control/saline, treatment at a dose of 50 mg/kg was can reverse this increase in diabetic group for EROs, while the TBARS both doses were effective. Thus, the results indicate that the LG was able to modulate the activity of ectonucleotidases well as the expression of P2X7 and A1 receptors and prevent the increase of the oxidative stress. This evidences the beneficial properties of Lingonberry extract, suggesting that this fruit may be coadjuvant in the treatment of diabetes.